Capture the flag challenge design and implementation – part 2 - Tan, Chuan Jie (Nanyang Technological University, 2023)
Originally designed as a form of cybersecurity training, Capture the Flag (CTFs) competitions are an effective means of introducing cybersecurity concepts while providing a fun and out of the box environment. With all the tests, assignments, and deadlines that students in tertiary education face, it often stifles creativity and promotes learning for grades rather than learning practical skills and abilities that can be useful for future growth. This is where CTFs come in as they provide a fun and innovative avenue for students to learn more and develop new skill sets that might not be taught in the normal classroom scenario. Recent CTFs focus more on making fun and educational challenges through gamifying cybersecurity concepts that are necessary to obtaining a solution. CTFs are increasingly being used in informal settings such as GoogleCTF as a form of competition but they are not frequently used for educational purposes in institutions of higher learning yet.